Avaliação das atividades antifúngica, citotóxica e mutagênica do geraniol contra espécies de candida spp. isoladas de pacientes com estomatite protética : uma análise in sílico e in vitro - Oliveira Júnior, José Klidenberg de (2024)
Introduction: Denture stomatitis is a common inflammatory disease in denture wearers that is often associated with infections caused by multidrug-resistant Candida species. Geraniol, a monoterpene found in essential oils of various plants, has shown promising antifungal properties for treating such conditions. Objective: To evaluate the antifungal activities of geraniol against Candida albicans and Candida Tropicalis species, to study its mechanisms of action, to carry out combination tests with nystatin and miconazole, and to evaluate its cytotoxicity in blood cells, mutagenicity and to carry out in silico studies by molecular docking. Methods: The antifungal activity of geraniol was evaluated by minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) tests using the broth microdilution method as recommended by the Clinical and Laboratory Standards Institute (CLSI). Sorbitol and ergosterol tests were performed to understand the mechanisms of action of geraniol. In the sorbitol assays, the change in MIC was evaluated in the presence of 0.8 M sorbitol. In the ergosterol tests, the MIC was determined in the presence of 400 μg/ml exogenous ergosterol. To determine fractional inhibitory concentration indices (FICI), combination studies with nystatin and miconazole were performed using the checkerboard method. Cytotoxicity was assessed in human erythrocytes of different blood groups (A, B, O) by hemolysis assays, while mutagenicity was examined in oral mucosal epithelial cells using micronucleus analysis and other genotoxic markers. Molecular docking was performed to predict the interactions between geraniol and key fungal cell proteins as well as its interaction with ergosterol. Results: Geraniol showed MIC values of 64 μg/ml for C. albicans and 32-64 μg/ml for C. tropicalis, comparable to the standard antifungals nystatin and miconazole. The fungicidal activity of geraniol was confirmed by MFCs with values of 128 μg/ml for C. albicans and 64-128 μg/ml for C. tropicalis. The MFC/MIC ratio of 1:1 or 2:1 confirms the fungicidal effect of geraniol. In the sorbitol tests, the MIC of geraniol against C. albicans increased from 64 μg/ml to 256 μg/ml, indicating that it disrupts the integrity of fungal cell walls. No change in MIC was observed in C. tropicalis in the presence of sorbitol. In the ergosterol assays, the MIC of geraniol increased significantly in the presence of exogenous ergosterol and ranged from 64 μg/ml to 256 μg/ml in both C. albicans and C. tropicalis, suggesting that geraniol interacts directly with ergosterol interacts in fungal plasma membranes. The combination of geraniol and nystatin showed predominantly indifferent effects, with the exception of the clinical strain LM-4B, in which an additive effect was observed (FICI = 0.625). The combination of geraniol and miconazole showed significant synergy in strain LM-4B (FICI = 0.25). Cytotoxicity tests revealed that geraniol did not cause significant hemolysis at low concentrations, while at higher concentrations (500–1000 μg/ml), hemolysis exceeded 80%. Mutagenicity analysis showed that geraniol caused cellular changes only at high concentrations, and molecular docking confirmed geraniol's interactions with key fungal cell proteins, suggesting mechanisms of action contributing to its antifungal efficacy. Conclusion: Geraniol proves to be a promising therapeutic alternative for the treatment of oral fungal infections and offers an effective and safe solution, especially in the treatment of denture stomatitis. However, use of higher concentrations should be done with caution due to the risk of cytotoxicity and mutagenicity. Further studies are required to define safe parameters and explore broader clinical applications, opening up new frontiers in dental product and therapy research.